Using reading to learn pedagogy to enhance the English first additional language teachers' classroom practice - Mawela, Rethabile Rejoice (Rhodes University, Faculty of Education, Department of Education, 2018)
Drawing from the Hallidayan, Bernsteinian and Vygotskyan theories of Systemic Functional Linguistics, Pedagogic Discourse and Social Learning, this study examined the role that Rose's (2005) Reading to Learn (RtL) pedagogy could play in the development of teachers' pedagogic practices in the teaching of English First Additional Language. The study participants teach English First Additional Language in Black, materially and economically disadvantaged rural primary schools in Kuruman, the Northern Cape Province, South Africa. As study participants, 4 intermediate phase and 4 senior phase teachers of English First Additional Language were purposively selected from 6 rural schools. Located within the Critical Paradigm, Subjective Epistemology and Mixed-Method approach, the study used documentary evidence, semi- structured interviews and RtL pedagogy as research instruments. Research findings reveal that RtL enriched and advanced teachers' pedagogic practice in the teaching of reading and writing. As a consequence, teachers' classroom practice of the 8 study participants improved as evidenced as their content knowledge expanded, the quality of teaching developed and their perceptions of themselves as professionals was transformed. An accompanying finding is that teachers acquired the tools to teach reading and the reading and writing proficiencies of learners in their classrooms improved.
Keywords: Reading to learn; Language transfer (Language learning) -- South Africa -- Kuruman; Language teachers -- South Africa -- Kuruman; Language and languages -- Study and teaching -- Bilingual method; Second language acquisition